Live cell in situ lysosomal GCase activity correlates to alpha-synuclein levels in human differentiated neurons with LRRK2 and GBA1 mutations - Labrador-Garrido, Adahir; Zhong, Siying; Hughes, Laura; Keshiya, Shikara; Kim, Woojin S.; Halliday, Glenda M.; Dzamko, Nicolas (Frontiers in Cellular Neuroscience, 2023)
Heterozygous mutations in GBA1, which encodes the lysosomal hydrolase glucocerebrosidase (GCase) are a common risk factor for the neurodegenerative movement disorder Parkinson's disease (PD). Consequently, therapeutic options targeting the GCase enzyme are in development. An important aspect of this development is determining the effect of potential modifying compounds on GCase activity, which can be complicated by different methods and substrate probes that are commonly employed for this purpose. In this study we have employed the GCase substrate probe 5-(pentafluorobenzoylamino)fluorescein di--D-glucopyranoside (PFB-FDGlu) in combination with live cell imaging to measure GCase activity in situ, in the lysosome. The live cell assay was validated using the GCase inhibitor conduritol-B-epoxide and with GBA1 knockout neural cells, and then used to assess GCase activity in iPSC differentiated to neural stem cells and neurons that were obtained from idiopathic PD patients and PD patients with the LRRK2 G2019S mutation and GBA N370S mutation, as well as controls (n=4 per group). Heterogeneity in GCase activity was observed across all groups, however, a significant inverse correlation between GCase activity and levels of alpha-synuclein protein was observed. The live cell imaging assay for GCase activity could be useful for further understanding the role of GCase in PD, as well as for screening of potential modifying compounds in differentiated human cell models.